Visionary Leadership of Kyai in Enhancing the Quality of Islamic Education at Islamic Boarding Schools in Jambi Province, Indonesia - Mursyid Musthofa An Najmi; Marwazi Marwazi; Jamaluddin Jamaluddin (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study explores the visionary leadership strategies of Kyai in enhancing the quality of Islamic education at Pondok Pesantren Daaru Attauhid, Raudhatul Mujawwidin, and Al Jauharen in Jambi Province, Indonesia. Employing a qualitative approach with a multi-site design, the study collected data through in-depth interviews, participant observations, and document analysis. Findings reveal that visionary Kyai leadership is characterized by strong vision, educational innovation, integration of diniyah and general curricula, and collaboration with external stakeholders. Key challenges include limited human resources, insufficient infrastructure, and lack of stakeholder engagement. The study recommends leadership training, institutional capacity development, and technological integration to address these challenges and support sustainable Islamic education.